The relation between sensation seeking, aggression and self-confidence with Needle stick and Sharp injuries among nurses - Rana Ghasemi; Hossein Ebrahimi; Roya Najafi-Vosough; Shaban Ghasemi; Jamshid Rahimi; Rezvan Abedinloo (PLoS ONE, 2025)
Background One of the most important occupational injuries experienced by nurses is needle sticks. The causes and factors of needle sticks are not fully known. This study was conducted with the aim of investigating the relationship between sensation-seeking, aggressiveness, and self-confidence with needle stick and Sharp injuries among nurses in a children’s and women’s hospital. Methods This cross-sectional study was conducted on 143 nursing personnel of a children’s and women’s hospital in Iran. To collect data, people were asked to complete several questionnaires, including a demographic questionnaire, Arnett questionnaire of Sensation Seeking, aggression characteristics questionnaire (AGQ), and Rosenberg’s self-confidence questionnaire. They were also asked about the number of injuries caused by nurses’ needles and Sharp injuries in the last 12 months. Data analysis was done using SPSS software (version 22). Results The results of this study showed, no relationship was between sensation seeking, aggression, and self-confidence with Needle sticks and Sharp injuries among nurses (P-value>0.05). Age and work experience have the inverse significant relationship with sensation seeking (P-value<0.05). The most common cause of needle sticks and sharp injuries was syringes (52.9%). Conclusions There is no relationship between sensation seeking, aggression, and self-confidence with Needle sticks and Sharp injuries among nurses. Nurses with high age and more work experience show less sensation-seeking. Needle sticks and Sharp injuries in nurses were mostly caused by syringes.